2021
DOI: 10.1186/s12877-021-02481-7
|View full text |Cite
|
Sign up to set email alerts
|

Serum concentrations of oxytocin, DHEA and follistatin are associated with osteoporosis or sarcopenia in community-dwelling postmenopausal women

Abstract: Background Osteoporosis and sarcopenia are major health issues in postmenopausal women due to their high prevalence and association with several adverse outcomes. However, no biomarkers may be used for screening and diagnosis. The current study investigated potential biomarkers for osteoporosis and/or sarcopenia in postmenopausal women. Methods A cross-sectional study on 478 healthy community-dwelling postmenopausal women aged 50–90 years was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 36 publications
0
31
0
Order By: Relevance
“…Of the 10 included studies, 4 were from Europe, 13–16 3 were from the United States 17–19 and 3 were from Asia 20–22 . The majority of the studies included middle aged or postmenopausal women; 1 study was of premenopausal women under 40 years of age 17 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 10 included studies, 4 were from Europe, 13–16 3 were from the United States 17–19 and 3 were from Asia 20–22 . The majority of the studies included middle aged or postmenopausal women; 1 study was of premenopausal women under 40 years of age 17 .…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the studies included middle aged or postmenopausal women; 1 study was of premenopausal women under 40 years of age 17 . Eight studies reported cross‐sectional associations between testosterone and muscle outcomes, 13–15,17–20,22 1 reported longitudinal associations, 21 and 1 reported both cross‐sectional and longitudinal associations 16 …”
Section: Resultsmentioning
confidence: 99%
“…Follistatin is an antagonist of TGF- β ligands, including myostatin and activin A, by acting on myogenic transcription factors. Follistatin has been correlated with muscle mass and muscle function in women in a small number of studies [ 28 , 31 ], but this association was not confirmed in men [ 28 ]. However, in mid- to long-term resistance training intervention trials, follistatin and/or follistatin/myostatin ratio were increased.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, as a biomarker of sarcopenia, DHEAS is the most studied steroid hormone. DHEAS is decreased in sarcopenia, while cortisol is increased, probably due to chronic inflammation [ 131 , 132 ]. Both DHEAS and cortisol blood levels have been shown to be modified by nutritional or nutritional-exercise interventional trials [ 133 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation